Enamel remineralisation-inducing materials for caries prevention - Sri Kunarti; Widya Saraswati; Dur Muhammad Lashari; Nadhifa Salma; Tasya Nafatila (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Dental caries is a multifactorial disease indicated by the progressive demineralisation process of dental tissue. It is caused by an imbalance between the remineralisation and demineralisation processes. The focus of caries management is on prevention. Providing materials that can induce remineralisation is one management of caries prevention. Various materials have been or are being researched, such as casein phosphopeptide amorphous calcium phosphate (CPP–ACP), tricalcium phosphate (fTCP), bioactive glass (BAG), and nanotechnologies such as nano-hydroxyapatite (n-HAP) and silver nano fluorine (NSF). Purpose: This study aims to review the development of enamel remineralisation inducing materials as a newer approach in caries prevention. Review: Various ingredients have been shown to increase enamel remineralisation through different mechanisms in preventing the development of carious lesions. Conclusion: CPP–ACP, fTCP, BAG, n-HAP, and NSF can induce enamel remineralisation as caries prevention agents. n-HAP and NSF are the most effective agents to enhance enamel remineralisation to prevent caries.